Nozick on Geographical Regulations: A Critique - Block, Walter E. Block (Journal of Critical Realism in Socio-Economics (JOCRISE), 2025)
Nozick claims that under free enterprise, it would be possible for a malevolent very rich person to buy up land surrounding his enemy, and not allow outside of this barrier, and to prevent anyone else travelling within it. Thus, this target would be cut off from all trade and interaction with anyone else. In effect, this would constitute legalized murder. The logical implication of this critique of laissez faire capitalism, this “market failure” would be that the government ought to pass a law preventing this type of encirclement.